Sex differences in the association between episodic memory residual reserve index and change in executive function - Cheyenne Chooi; Brandon E. Gavett; David Ames; Paul Maruff; Vincent Doré; Victor L. Villemagne; Pierrick Bourgeat; Ying Xia; Colin L. Masters; Ralph N. Martins; Kevin Taddei; Christopher C. Rowe; et al. (Aging Brain, 2025)
Sex differences in cognitive reserve might contribute to females being disproportionately affected by Alzheimer’s disease (AD). We investigated sex differences in the protective effects of cognitive reserve, and whether brain beta-amyloid accounts for differences. Older adults (n = 997 from the Australian Imaging, Biomarkers and Lifestyle Study of Ageing) diagnosed as Cognitively Normal, Mild Cognitive Impairment, or AD at baseline were assessed every 18 months for up to a maximum of seven visits. Cognitive reserve was calculated from the variance in episodic memory not explained by demographic or brain measures. Executive functioning (EF) intercept and slope were regressed onto the main and interaction effects of cognitive reserve x brain integrity x sex, plus covariates (age, number of APOE ε4 alleles). A three-way interaction was observed between cognitive reserve, brain integrity, and sex on the EF slope. Females benefitted more than males from the protective effects of cognitive reserve at low levels of brain integrity. Sex differences in the protective effect of cognitive reserve were not moderated by brain beta-amyloid burden.